In Search of Sources in Jacobus Handl’s Opus Musicum: The “Instructio ad Musicos” and Its Significance in Relation to the Composer’s Plan - Desmet, Marc (De musica disserenda, 2018)
Jacobus Handl-Gallus mentions five of his own motets in the “Instructio ad musicos” placed at the beginning of Opus musicum, volume 3, in order to explain what his plan was. A close examination of these motets reveals that the texts themselves do not follow a strict liturgical prescription, which leads to the conclusion that we actually have here settings bearing the personal stamp of the composer. These examples provide useful clues leading one to reconsider the sources for the entire collection. The contents of the Opus musicum may indeed prove far less homogeneous than one might initially infer from their impeccable distribution according to the liturgical calendar. Jacobus Handl - Gallus v besedilu »Instructio ad musicos« z začetka tretjega zvezka zbirke Opus musicum omenja pet svojih motetov z namenom, da pojasni svoj načrt. Natančen pregled besedil teh motetov razodeva, da teksti sami niso popolnoma v skladu z liturgično redakcijo, kar napeljuje k podmeni, da imamo opravka s priredbami, ki nosijo skladateljev osebni pečat. Zdi se, da je vsebina zbirke Opus musicum precej manj homogena, kot se kaže v razporeditvi po liturgičnem koledarju.